8дм-59см+3дм6см= 77см-29см+1дм9см= 9дм3см-2дм-1дм7см= 3дм6см - 2дм8см + 14см- 9см = 5дм8см+9см-36см=

HamzaT5050 HamzaT5050    3   04.09.2019 06:40    1

Ответы
moonlight2812 moonlight2812  06.10.2020 16:21
8дм- 59см + 3дм6см = 57см
77см-29см + 1дм9см = 67см
9дм3см - 2дм-1дм7см = 5дм 6см
3дм6см - 2дм8см + 14см - 9см = 13см
5дм8см + 9см - 36см = 31см
ПОКАЗАТЬ ОТВЕТЫ
KiskaSofia KiskaSofia  06.10.2020 16:21
8дм-59см+3дм6см=
77см-29см+1дм9см=
9дм3см-2дм-1дм7см=
3дм6см - 2дм8см + 14см- 9см =
5дм8см+9см-36см=
8дм-59см+3дм6см= 77см-29см+1дм9см= 9дм3см-2дм-1дм7см= 3дм6см - 2дм8см + 14см- 9см = 5дм8см+9см-36см=
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика